Raízes antropológicas do preconceito religioso: diálogo com Darcy Ribeiro - Koury, Jussara Rocha (2017)
The aim of the present study is to analyze some aspects of the origin of religious prejudice, found in the anthropological constitution of the Brazilian people in their originating matrices – the Brazilian indigenous, the Portuguese and the Black – as well as to inquire about the formation of our popular religiosity in order to understand the violence of Brazilian religious prejudice in relation to its African matrices. To do so, we used a qualitative approach and carried out our research through literary review as we wished to investigate, as far as possible, the socio-anthropological context that resulted (and still results at present) in implicit and/or explicit intolerance to Afro-Brazilian religious expressions. We seek shelter in Darcy Ribeiro‟s work because it is, if not the most important, one of the keys to understanding the ethnic and cultural formation of the Brazilian people. Our first concern was to inquire as to why a country as plural as ours is, at the same time, a bigoted country, at all levels of social relations, including the Afro-Brazilian religious practices. What is revealed, step by step, is the role that was played by the Catholic Church in the formation of religious prejudice, particularly with relation to the religions of African and indigenous matrices. The Catholic religion, like others with Jewish-Christian roots, adopts, in her monotheistic expression, the idea of a people chosen by the Only and True God. Thus, she expresses itself with a natural attitude of superiority over other peoples, dictating thought and behavior. And so, the Brazilian people repeat as they have learned: there is salvation only in the Jewish-Christian tradition. There is no room for questioning. The vision of all people as the children of God finds no place in this discussion. Is prejudice justified in this way? No. With awareness, one can understands its roots in order to build another kind of relationship with the originating matrices of the Brazilian people, in the hope of retrieving our identity also in the religious aspect.